Amorphous calcium phosphate nanowires prepared using beta-glycerophosphate disodium salt as an organic phosphate source by a microwave-assisted hydrothermal method and adsorption of heavy metals in water treatment. Issue 50 (4th June 2015) - Ding, Guan-Jun; Zhu, Ying-Jie; Qi, Chao; Sun, Tuan-Wei; Wu, Jin; Chen, Feng
<x xml:space="preserve">Abstract</x> Amorphous calcium phosphate nanowires were prepared using β-glycerophosphate disodium salt as the phosphate source by a microwave-assisted hydrothermal method.